Differences in microbial profile of endometrial fluid and tissue samples in women with in vitro fertilization failure are driven by Lactobacillus abundance. (28th January 2022) - Lüll, Kreete; Saare, Merli; Peters, Maire; Kakhiani, Ekaterina; Zhdanova, Anastasia; Salumets, Andres; Boyarsky, Konstantin; Org, Elin
Abstract: Introduction: The endometrial microbiota has been linked to several gynecological disorders, including infertility. It has been shown that the microbial profile of endometrium could have a role in fertilization and pregnancy outcomes. In this study we aim to assess the microbial community of endometrial tissue (ET) and endometrial fluid (EF) samples in women receiving in vitro fertilization (IVF) treatment. We also search for possible associations between chronic endometritis (CE) and endometrial microbiota. Material and methods: This was a cohort study involving 25 women aged between 28 and 42 years with both primary and secondary infertility and with at least one IVF failure. The ET and EF sample collection was carried out between September 2016 and November 2018. Each of the participants provided two types of samples—tissue and fluid samples (50 samples in total). A 16S rRNA sequencing was performed on both of the sample types for microbial profile evaluation. CE was diagnosed based on a CD138 immunohistochemistry where CE diagnosis was confirmed in the presence of one or more plasma cells. Microbial profiles of women with and without CE were compared in both sample types separately. Results: We report no differences in the microbial composition and alpha diversity ( p Observed  = 0.07, p Shannon  = 0.65, p Inverse Simpson  = 0.59) between the EF and ET samples of IVF patients. We show that the abundance of the genus Lactobacillus influences the variation in microbial beta diversity between and fluid samples ( r 2  = 0.34; false discovery rate [FDR] <9.9 × 10 −5 ). We report that 32% (8/25) of the participants had differences in Lactobacillus dominance in the paired samples and these samples also present a different microbial diversity ( p Shannon  = 0.06, FDRweighted UniFrac  = 0.01). These results suggest that the microbial differences between ET and fluid samples are driven by the abundance of genus Lactobacillus . The microbiome of CE and without CE (ie non‐CE) women in our sample set of IVF patients was similar. Conclusions: Our findings show that genus Lactobacillus dominance is an important factor influencing the microbial composition of ET and fluid samples.